2016
DOI: 10.1542/peds.2016-0775
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Growth Restriction and Cognitive Impairment

Abstract: BACKGROUND: Although both fetal and long-term growth restriction are well documented in fetal alcohol spectrum disorders, effects on pattern of growth trajectory have not been characterized. Furthermore, the degree to which growth trajectories are related to fetal alcohol-related neurocognitive deficits is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 34 publications
5
76
1
3
Order By: Relevance
“…We found an inverse association between maternal alcohol use in the first trimester and BFP at age 6 years following adjustment for confounders. Heavy alcohol exposure during early life or prepregnancy is associated with reduced birthweight and adverse pregnancy outcomes, which may have a persistent influence on childhood growth. A recent study of over 7000 British mother‐child dyads (ALSPAC birth cohort) demonstrated a similar association in young children; however, this was no longer evident at the age of 10 years .…”
Section: Discussionmentioning
confidence: 99%
“…We found an inverse association between maternal alcohol use in the first trimester and BFP at age 6 years following adjustment for confounders. Heavy alcohol exposure during early life or prepregnancy is associated with reduced birthweight and adverse pregnancy outcomes, which may have a persistent influence on childhood growth. A recent study of over 7000 British mother‐child dyads (ALSPAC birth cohort) demonstrated a similar association in young children; however, this was no longer evident at the age of 10 years .…”
Section: Discussionmentioning
confidence: 99%
“…Immediately following EAE, AB strain larvae displayed mild growth restriction, consistent with the short stature phenotypes typical of human FAS (Supplemental Figure 2, A-C, and ref. 34). When removed from ethanol, larvae exhibited compensatory growth and reached the same size as control-matched siblings by 20 dpf (Supplemental Figure 2D).…”
Section: Introductionmentioning
confidence: 99%
“…Our prior findings linking growth trajectory pattern to severity of neurocognitive impairment in FASD (Carter et al, 2016a) suggest that deficits in growth and neurobehavior may share common mechanisms. Future studies are needed to determine whether the alcohol-related alterations in gene expression that we have found to be related to somatic growth play a role in fetal alcohol neurobehavioral deficits in humans.…”
Section: Igf2mentioning
confidence: 82%
“…Three summary measures were constructed by averaging across pregnancy: oz AA/d; oz AA/occasion; and frequency of drinking. We have previously validated this ascertainment protocol in relation to levels of fatty acid ethyl esters in meconium samples in this community (Bearer et al, 2003) and in relation to a broad range of infant (Jacobson et al, 2002) and child outcomes (e.g., Carter et al, 2016a;Jacobson et al, 2008;Lindinger et al, 2016;Meintjes et al, 2014).…”
Section: Ascertainment Of Maternal Alcohol Smoking and Drug Usementioning
confidence: 99%
See 1 more Smart Citation